2020
DOI: 10.1186/s13018-020-01924-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of immediate programmed cryotherapy and continuous passive motion in patients after computer-assisted total knee arthroplasty: a prospective, randomized controlled trial

Abstract: Background: The postoperative nursing intervention with immediate cryotherapy and continuous passive motion (CPM) remains elusive regarding the postoperative pain and range of motion (ROM) for patients undergoing computer-assisted total knee arthroplasty (CAS-TKA). Methods: A prospective, randomized controlled trial with a purposive sampling method was utilized. Sixty patients scheduled for a unilateral CAS-TKA at a medical center were randomly assigned to the intervention group (n = 30) and control group (n =… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The effects of cryotherapy were not significantly different in six studies (Brouwers et al, 2022; Chen et al, 2020; Hecht et al, 1983; Holmström & Härdin, 2005; Thijs et al, 2019; Webb et al, 1998). However, in one, the swelling decreased in the cryotherapy group compared to the control group after 24 and 48 h (Wang, 2017).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The effects of cryotherapy were not significantly different in six studies (Brouwers et al, 2022; Chen et al, 2020; Hecht et al, 1983; Holmström & Härdin, 2005; Thijs et al, 2019; Webb et al, 1998). However, in one, the swelling decreased in the cryotherapy group compared to the control group after 24 and 48 h (Wang, 2017).…”
Section: Resultsmentioning
confidence: 94%
“…The application time per session was 10 min in Stocker et al (2018). It was 20 min for Chen et al (2020) and Hecht et al (1983), 2–6 h for Brouwers et al (2022), 6 h for Thijs et al (2019), 48 h for Holmström and Härdin (2005) and Wang (2017). One study did not provide the application time per session (Webb et al, 1998).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Continuous passive motion (CPM) is an adjunct therapy for the initiation of early mobilization of the operated knee in patients that underwent TKA [ 30 , 31 ]. Adequate postoperative pain management encourages patients to participate in the CPM rehabilitation program [ 32 ] and facilitates a faster recovery to normal activities [ 33 ]. In addition, our study found that more patients in Group A quit their first CPM training because of intolerable pain after the first few cycles of passive motion training; these patients also had higher VAS scores than patients with ACB.…”
Section: Discussionmentioning
confidence: 99%